Sensitization processes in materials based on compounds containing a Xe-O bond - Kondratenko, P.A.; Lopatkin, Yu.M.; Sakun, T.N. (Functional Materials, 2008)
The work contains the results of experimental and theoretical studies of the sensitization processes in compounds with the Xe-O type bond between the molecule fragments. Such a bond is formed between a molecule containing completely occupied molecular orbitals and another one being in the triplet ground state. Such molecules include diazonium salts, azides, as well as molecules comprising a heteroatom with localized n-orbital to which an oxygen atom is connected. The studies have shown that all such compounds inherit a series of XeO molecule features, namely, exhibit a photochemical activity and might be photosensitized. The sensitization possibilities according to the electron transfer and energy transfer mechanisms as well as the chemical sensitization have been considered. All three sensitization types have been shown to be possible in diazonium salts. This is due to the fact that the dissociative state of diazonium cation is the lower excited state and, moreover, the an additional electron is localized on that state. For azides and molecules comprising an N-O bond, the sensitization according to the energy transfer mechanism is only possible except for the sensitization to hard radiation, when the electron capture becomes possible on the dissociative state of the photo-active molecule being a high-excited state. Робота містить результати експериментальних і теоретичних досліджень процесів сенсибілізації фотолізу сполук зі зв'язком типу Хе-O між фрагментами молекули. Такий зв'язок виникає між молекулами, одна з яких має повністю зайняті молекулярні орбіталі, а друга знаходиться в основному триплетному стані. До таких молекул належать солі діазонію, азиди, а також молекули з гетероатомом, на якому локалізована п-орбіталь, по якій приєднаний атом кисню. Дослідження показали, що всі ці сполуки мають фотохімічну активність і допускають сенсибілізацію світлочутливості. Розглянуто можливості сенсибілізації за механізмами перенесення електрона, перенесення енергії, а також хімічної сенсибілізації. Показано, що для солей діазонію можна здійснити сенсибілізацію всіх трьох типів. Це обумовлено тим, що дисоціативний стан катіона діазонію є нижнім збудженим станом і, крім того, на цьому стані локалізується додатковий електрон. Для азидів і молекул із зв'язком N-O можлива сенсибілізація тільки за механізмом перенесення енергії, за винятком випадку сенсибілізації до жорсткого випромінювання, коли з'являється можливість захоплення електрона на дисоціативний стан фотоактивної молекули, який є високозбудженим станом. Работа содержит результаты экспериментальных и теоретических исследований процессов сенсибилизации фотолиза соединений со связью типа Хе-О между фрагментами молекулы. Такая связь возникает между молекулами, одна из которых имеет полностью занятые молекулярные орбитали, а вторая находится в основном триплетном состоянии. К числу таких молекул относятся соли диазония, азиды, а также молекулы с гетероатомом, на котором локализована п-орбиталь, по которой присоединен атом кислорода. Исследования показали, что все эти соединения обладают фотохимической активностью и допускают сенсибилизацию светочувствительности. Рассмотрены возможности сенсибилизации по механизму переноса электрона, переноса энергии, а также химической сенсибилизации. Показано, что для солей диазония можно осуществить сенсибилизацию всех трех типов. Это обусловлено тем, что диссоциативное состояние катиона диазония является нижним возбужденным состоянием и, кроме того, на этом состоянии локализуется дополнительный электрон. Для азидов и молекул со связью N-O возможна сенсибилизация только по механизму переноса энергии, за исключением случая сенсибилизации к жесткому излучению, когда появляется возможность захвата электрона на диссоциативное состояние фотоактивной молекулы, которое является высоковозбужденным состоянием.